Hypokinesia upon Pallidal Deep Brain Stimulation of Dystonia: Support of a GABAergic Mechanism - Amtage, Florian; Feuerstein, Thomas J.; Meier, Simone; Prokop, Thomas; Piroth, Tobias; Pinsker, Marcus O. (Frontiers in Neurology, 2013)
In the past, many studies have documented the beneficial effects of deep brain stimulation (DBS) in the globus pallidus internus for treatment of primary segmental or generalized dystonia. Recently however, several reports focused on DBS-induced hypokinesia or freezing of gait as a side effect in these patients. Here we report on two patients suffering from freezing of gait after successful treatment of their dystonic movement disorder with pallidal high frequency stimulation (HFS). Several attempts to reduce the freezing of gait resulted in worsening of the control of dystonia. In one patient levodopa treatment was initialized which was somewhat successful to relieve freezing of gait. We discuss the possible mechanisms of hypokinetic side effects of pallidal DBS which can be explained by the hypothesis of selective GABA release as the mode of action of HFS. Pallidal HFS is also effective in treating idiopathic Parkinson’s disease as a hypokinetic disorder which at first sight seems to be a paradox. In our view, however, the GABAergic hypothesis can explain this and other clinical observations.